2014
DOI: 10.1055/s-0038-1623239
|View full text |Cite
|
Sign up to set email alerts
|

Torsio uteri beim Rind – Therapie und Folgen für das Kalb und die Kuh

Abstract: Zusammenfassung Ziel dieser Arbeit ist, den derzeitigen Stand der Literatur über die Therapie der Torsio uteri sowie die Folgen für Kuh und Kalb darzustellen. Material und Methode: Ausgewertet wurde die Literatur, die in Online-Suchportalen (Pub Med, Medline) und veterinärmedizinischen Fachzeitschriften sowie einschlägigen Lehrbüchern zur Verfügung steht. Ergebnisse: Die Therapie besteht zunächst im Versuch der Retorsion des Uterus, wobei direkte und indirekte Retorsionsmethoden zur Verfügung stehen,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
2
0
4
Order By: Relevance
“…Some authors stated that when diagnosing uterine torsion, it is better to immediately proceed to a caesarean section, at most a few hours after the first signs of parturition, especially in water buffalos (Alfaris et al, 2014; Mohteshamuddin et al, 2014), than to try to return the uterus to its previous, normal position (Krishnakumar et al, 2008). Opposite to the previous statement, other authors suggested to proceed with a detorsion technique first, and then, were it to fail, to performing a caesarean section to save the life of both the calf and the cow (Erteld et al, 2014). In this case report, we found that the right side uterine torsion was more often than the left side uterine torsion, which are similar to findings reported by Moore and Richardson (1995).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors stated that when diagnosing uterine torsion, it is better to immediately proceed to a caesarean section, at most a few hours after the first signs of parturition, especially in water buffalos (Alfaris et al, 2014; Mohteshamuddin et al, 2014), than to try to return the uterus to its previous, normal position (Krishnakumar et al, 2008). Opposite to the previous statement, other authors suggested to proceed with a detorsion technique first, and then, were it to fail, to performing a caesarean section to save the life of both the calf and the cow (Erteld et al, 2014). In this case report, we found that the right side uterine torsion was more often than the left side uterine torsion, which are similar to findings reported by Moore and Richardson (1995).…”
Section: Discussionmentioning
confidence: 99%
“…Zu den direkten Retorsionsmethoden zählen der Kamer'sche Griff und der Hebegriff, die Methoden nach Snöborg oder Auer und Schreiner, die Verwendung der Torsionsgabel nach Caemmerer, des Torsionshakens nach Kalchschmidt oder des GYN-stick®. Zu den indirekten Retorsionsmethoden gehören die Brettwälzmethode, das Wälzen mit vaginaler Fixation und die Laparotomie (2,5,7). In der vorliegenden Arbeit gelang die direkte Retorsion fast immer allein durch manuelle Kraftaufwendung mittels Kamer'schem Griff und/oder Hebegriff.…”
Section: Diskussionunclassified
“…Das einzige Hilfsmittel, das häufig Verwendung fand, war ein Augenhaken. Wenn die Kraft des Tierarztes für eine manuelle Retorsion nicht ausreicht, die Gliedmaßen des Kalbes aber zu erreichen sind, können Torsionsgabel oder Torsionshaken eingesetzt werden (5). Ein der Torsionsgabel ähnliches, neueres Instrument stellt der GYN-stick® dar (3).…”
Section: Diskussionunclassified
See 2 more Smart Citations